The influence of attitude, social norms on adaptation practices of oil palm smallholders, and mediation role of intention towards climate change impact in Malaysia - Man, Norsida; Shehu, Nabara Isah; Kamarulzaman, Nitty Hirawaty; Sulaiman, Zulkefly (IJSTR, 2019)
The study examines the influence of attitude, social norms on adaptation practices of oil palm smallholders and mediation role of intention towards climate impact in Malaysia. Using a multistage cluster sampling technique, a total of 397 respondents were chosen. For data collection, a structured questionnaire was used and analyzed using SPSS and AMOS graphics. The study has shown the relationships between the variables using the theory of reasoning Action (TRA). It however, revealed attitude (r = 0.167, P < 0.004), social norms (r = 0.389, P < 0.000), intention (r = 0.163, P < 0.005) and adaptation practice. However, it revealed the contribution of attitude (β= 0.124, p < 0.014), social norms (β = 0.203, p < .000), intention (β = 0.292, p < 000) and adaptation practice. Similarly, the study revealed the mediation role of intention in the relationship between attitude (β = 0.036, LB = 0.007 and UB = 0.086, P = 0.016), social norms (β = 0.059, LB = 0.021 and UB = 0.124, P = 0.059), and adaptation practices at 95% bootstrapped confidence intervals. The study also revealed R2 value 0.45 indicating 45% of the variance explained in adaptation practice. On the other hand, the R2 value for intention 0.32 indicating 32%, of the variance explained in intention. The research concludes that the adaptation techniques of smallholder farmers in Malaysia are promoted socially and psychologically at various levels due to the attitude, social norms and intentions of the smallholder in the adaptation practice. The research, therefore, suggested that the Malaysian Palm Oil Board (MPOB) develop a training model to motivate all interested oil palm farmers with good farming practices (GAP) and weather reporting expertise so that Malaysian oil palm smallholder farmers can enhance their adaptation practices.